Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

there are given 3 equations (they are connected with cyclic codes): $$s(x)=v(x)+q(x)g(x)$$ $$g(x)h(x)=x^7+1$$ $$s(x)=v(x)h(x)\bmod(x^7+1)$$

I have following data (for $GF(8)$ with generator polynomial $p(x)=x^3+x+1$): $$g(x)=x^4+\alpha^3x^3+x^2+\alpha x+\alpha^3$$ $$q(x)=\alpha^6 x^2 + \alpha^2 x + \alpha$$ $$v(x)=\alpha^6 x^6 + \alpha^3 x^3 + \alpha^6 x^2 + x + \alpha^4$$

So I use first equation and: $$s(x)=v(x)+q(x)g(x)$$$$=(\alpha^6 x^6 + \alpha^3 x^3 + \alpha^6 x^2 + x + \alpha^4)+(\alpha^6 x^2 + \alpha^2 x + \alpha)(x^4+\alpha^3x^3+x^2+\alpha x+\alpha^3)$$ $$=(\alpha^6 x^6 + \alpha^3 x^3 + \alpha^6 x^2 + x + \alpha^4)+(\alpha^6 x^6 + \alpha^3 x^3 + \alpha^6 x^2 + \alpha^3x + \alpha^4)=\alpha x$$

And it's all right until now - result is correct. Now let's see second equation:

$$h(x)=\frac{x^7+1}{g(x)}=x^3+\alpha^3x^2+\alpha^2x+\alpha^4$$

And using third equation:

$$s(x)=v(x)h(x)\bmod(x^7+1)$$

$$s(x)=(\alpha^6 x^6 + \alpha^3 x^3 + \alpha^6 x^2 + x + \alpha^4)(x^3+\alpha^3x^2+\alpha^2x+\alpha^4)\bmod(x^7+1)$$

$$s(x)=\alpha^6 x^9 + \alpha^2 x^8 + \alpha x^7 + \alpha x^4 + \alpha^4 x^3 + \alpha^4 x^2 + \alpha^3 x + \alpha \bmod (x^7+1)$$

$$\frac{\alpha^6 x^9 + \alpha^2 x^8 + \alpha x^7 + \alpha x^4 + \alpha^4 x^3 + \alpha^4 x^2 + \alpha^3 x + \alpha}{x^7+1}$$$$=(\alpha^6 x^2 + \alpha^2 x + \alpha) + (\alpha x^4 + \alpha^4 x^3 + \alpha^3 x^2 + \alpha^5 x)$$

so

$$s(x)=\alpha x^4 + \alpha^4 x^3 + \alpha^3 x^2 + \alpha^5 x$$

Problem is that the result of $s(x)$ calculated with first and third equations is not the same. It should be the same for $s(x)$ of degree less than degree of $g(x)$.

share|improve this question
1  
+1 for typing all that out! –  Chris Taylor May 25 '11 at 11:32
add comment

1 Answer 1

up vote 3 down vote accepted

Your third equation should be $\rm\ s(x)\ h(x)\equiv v(x)\ h(x)\ \ (mod\ x^7 + 1)\:,\:$ which agrees with the calculations. It arises by multiplying the first equation by $\rm\:h(x)\:,\:$ then using the second equation.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.